Flow-mediated vasodilation and dietary intake of n-3 polyunsaturated acids in healthy subjects - Petersen, M. M.; Eschen, R. B.; Aardestrup, I.; Obel, T.; Schmidt, E. B. (Cellular and Molecular Biology, 2010)
Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), the two major marine n-3 polyunsaturated fatty acids (PUFA), have been proposed to decrease the risk of atherosclerosis and coronary heart disease. An early event during atherogenesis is endothelial dysfunction. We studied the correlation between fish consumption, serum phospholipid (sPL) levels of DHA and EPA and flow-mediated vasodilation (FMD), a measure of endothelial function. Furthermore, subjects were classified according to whether they did (Fish+, n = 19) or did not (Fish-, n = 21) follow the Danish recommendations, consuming at least 300 g fish/week. Neither the fish intake, sPL EPA nor sPL DHA significantly correlated with FMD, -0.20 (p = 0.23), -0.23 (p = 0.15) and -0.06 (p = 0.72), respectively. Also, when comparing the Fish+ and the Fish- group we did not find any significant differences in FMD (p = 0.33). In conclusion, our results did not show any correlation between intake and sPL levels of marine n-3 PUFA and FMD in healthy subjects.